Konsep Keadilan Pada Pernikahan Poligami : Analisa Politik Hukum Islam di Indonesia - Zulkifli Nas (Tabayyanu : Journal Of Islamic Law, 2024)
Polygamous marriage is a form of marriage that has existed in human civilization for centuries. A husband has more than one wife so the potential for being unfair to his wives and children is very possible. Therefore, there is a need for a concept of justice in polygamous marriages and a policy is needed to formulate and implement it in society. The problem in this research is what is the concept of justice in polygamous marriages according to Islamic philosophers and legal experts ? What is the politics of Islamic law in Indonesia so that justice is realized in polygamous marriages ? The aim of this research is to formulate the concept of justice in polygamous marriages and explain the legal politics to realize justice in polygamous marriages in Indonesia. Philosophers and Islamic legal experts agree that the concept of justice in polygamous marriages is moral justice (al-qistu al-fardi) and social justice (al-adlu al-jama'i). There are two Islamic legal policies to realize justice in polygamous marriages, namely first formulating the rules for polygamous marriages written in Law No.1/1974, PP No.9/1975 and KHI, and secondly state and government intervention to grant permits for polygamy, determining the reasons may engage in polygamy, determine the conditions for polygamy and ratify the contents of the marriage agreement.